Scientometric analysis of the emerging technology landscape - I’Anson, Ian (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
For researchers and decision makers in any technical domain, understanding the state of their area of interest is of critical importance. This „landscape‟ of emerging technologies is constantly evolving, and the sheer scale of research publication output in the modern era makes qualitative review increasingly difficult. Scientometric analysis is a valuable tool for the quantitative analysis of research output, and is employed by the Defence Science and Technology Laboratory (Dstl) Knowledge and Information Services in support of our research activities, for applications including identifying opportunities for academic collaboration, and technology watching/forecasting to identify emerging technologies and opportunities that may have implications for UK Defence. This paper provides an overview of our approach to conducting scientometric analysis of research papers and patent submissions. The methods for extracting and disambiguating publications are described, and the qualitative inferences we seek to make, along with some of the associated limitations and potential pitfalls are also discussed.